Penerapan Pemberian Topikal Madu Kaliandra terhadap Jaringan Nekrotik pada Luka Diabetes Mellitus di Puskesmas Pucangsawit - Anggun Rizkya Safitri; Sri Hartutik (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Background: Indonesia. The number of cases of diabetes mellitus in Indonesia continues to increase every year, the prevalence of diabetes mellitus in Indonesia is 10.7 million in 2020. Topical administration of Kaliandra honey can reduce necrotic tissue in ulcer wounds because it contains antibacterial, antioxidant and anti-inflammatory. Objective : To describe the results of observations of topical administration of Kaliandra honey on diabetes mellitus wounds. Method : This study method uses a descriptive design and uses a Bates Jensen research sheet. In the topical administration method of Kaliandra honey, what is measured is necrotic tissue in wounds that have been given intervention for 14 days. Results : After topical administration of Kaliandra honey to the two respondents who had diabetic wounds for 14 days, it showed a reduction in necrotic tissue in the wounds. Conclusion : Topical application of Kaliandra honey to diabetes mellitus wounds can reduce necrotic tissue.